Citrus Diseases Exotic to Florida: Sweet Orange Scab (SOS) - Kuang-Ren Chung; Lavern W. Timmer (EDIS)
Sweet Orange Scab is a disease that differs in host ranges from the common citrus scab present in Florida. Citrus scab is serious on many tangerines and tangerine hybrids such as Temple, as well as grapefruit and lemons, but rarely causes lesions on sweet orange. In contrast, SOS can cause significant damage on all sweet oranges as well as tangerines and their hybrids. It can be a significant problem on fruit produced for fresh market. Establishment of SOS in Florida could also have quarantine implications for marketing of fresh fruit, especially in Europe. SOS is common in humid citrus growing areas of South America (Argentina, Bolivia, Brazil, Ecuador, Paraguay, and Uruguay), but its presence has not been confirmed elsewhere. This document is Fact Sheet PP-224, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: November 2005.